Analysis of Factors Related to The Accuracy of Triage Assessment at The Emergency Room - Kartika Sari, Nurul; Mustamu, Alva Cherry (Universitas Nahdlatul Ulama Surabaya, 2023)
Triage assessment in the emergency department plays an important role in providing appropriate and effective services for emergency patients. However, the factors that affect the accuracy of triage assessments still need to be further understood, especially in the context of the COVID-19 pandemic. This study aims to analyze the relationship between nurse response time, nurse knowledge level, and respondent characteristics with the accuracy of triage assessment in the emergency room. This study used an analytical observational approach with a cross-sectional study approach. The sample consisted of 24 emergency room nurses who were selected using a nonprobability sampling technique, namely consecutive sampling. Data were collected through questionnaires and observation sheets and analyzed using the chi-square test. The analysis showed that nurse response time had a significant relationship with the accuracy of triage scoring (p<0.001). In addition, the level of knowledge of nurses was also significantly relatedto the accuracy of triage assessment (p = 0.017). However, no significant association was found between respondent characteristics such as age, gender, and education and the accuracy of triage assessments. The results of this study concluded that nurse response time and nurse knowledge level contributed to the accuracy of triage assessment in the emergency room. Nonetheless, respondent characteristics such as age, gender, and education did not affect the accuracy of triage scoring. This research provides adeeper understanding of the factors that influence the accuracy of triage assessments, which can help improve the quality of emergency services and more accurate decision-making in emergency departments